2018
DOI: 10.1097/01.ogx.0000549830.07599.6f
|View full text |Cite
|
Sign up to set email alerts
|

Association of Histologic Chorioamnionitis With Perinatal Brain Injury and Early Childhood Neurodevelopmental Outcomes Among Preterm Neonates

Abstract: IMPORTANCE Understanding the role of chorioamnionitis, a major factor leading to preterm birth, in the pathogenesis of neonatal brain injury and adverse neurodevelopmental outcomes may help in identifying potentially modifiable perinatal variables affecting brain health and outcomes among children born preterm. OBJECTIVE To evaluate whether histologic chorioamnionitis among neonates born very preterm is associated with intraventricular hemorrhage (IVH) and punctate white matter injury (WMI) or with adverse neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Our data largely confirm data from previous population studies obtained in very preterm infants suggesting that the adverse effects of histological chorioamnionitis on infant neurodevelopmental outcomes are mainly related to the complications of prematurity rather than to a direct effect of histologically diagnosed placental inflammation on the brain of preterm fetuses. 11,12 According to these suggestions, Bierstone et al 13 in a cohort multicenter study of neonates 32 weeks' gestational age confirmed that gestational age-related neonatal complications attenuate the apparent adverse effect of chorioamnionitis on infant neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our data largely confirm data from previous population studies obtained in very preterm infants suggesting that the adverse effects of histological chorioamnionitis on infant neurodevelopmental outcomes are mainly related to the complications of prematurity rather than to a direct effect of histologically diagnosed placental inflammation on the brain of preterm fetuses. 11,12 According to these suggestions, Bierstone et al 13 in a cohort multicenter study of neonates 32 weeks' gestational age confirmed that gestational age-related neonatal complications attenuate the apparent adverse effect of chorioamnionitis on infant neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 94%
“…8,9 Surprisingly, with the only possible exception of chorioamnionitis, studies on placental lesions of VLBW infants are mostly incomplete, represented by small case series or case-control investigations. 10 The role of chorioamnionitis as an adverse factor in developmental outcomes of VLBW is controversial, [11][12][13] whereas FVM and abruptio placentae have been associated with early markers of infant brain damage. 14,15 The recognition of placental features associated with neurodevelopmental impairment of VLBW could be very useful to identify newborns requiring proper neurodevelopmental follow-up due to an increased risk of developing neurodevelopmental impairments.…”
Section: Introductionmentioning
confidence: 99%
“…A large study of 2390 extremely preterm infants (born <27 weeks' gestational age) from sixteen centers across the United States found infants exposed to histological and clinical chorioamnionitis had an increased risk of cognitive impairment at 18-22 months' corrected age [10]. A separate study of 350 infants found that while gestational age was significantly lower among those with exposure to histological chorioamnionitis, there was no association with intraventricular hemorrhage, white matter injury around birth, or differences in cognitive or motor outcomes at 18-24 months' corrected age [11]. Additional studies have found weak causal or associative roles of chorioamnionitis with cerebral palsy risk [12] and no increased risk of white matter injury on magnetic resonance imaging (MRI) following histological chorioamnionitis in premature infants [13].…”
Section: Chorioamnionitis/intra-amniotic Infection (Iai)mentioning
confidence: 98%
“…variations in cortical thickness). But research continues to emphasize that postnatal complications from infections, particularly when associated with hypotension in the premature newborn, are associated with an increased risk of white matter injury [33,34].…”
Section: Predisposing Factors For Brain Injurymentioning
confidence: 99%